(untitled) (Al-Academy, 2023)
The current research deals with an analytical study of the ceramic works of one of the most important Japanese cities in the ceramics industry, which is the city (Dachi-Cho), which is characterized by a special and unique style from the rest of the other Japanese cities, as it uses special techniques for its potters and the families to which they belong, such as the technique of grafting and neriage. And printing graphics on ceramic pots. These and other techniques have spread in various countries of Asia and Europe, all the way to America, and transformations and revolutions have begun in these techniques until they have reached the point of absurdity. With all this scientific and technological development, the city (Dachi-Chu) remained committed to And preserving the rules of its cultural and social identity in the design and implementation of ceramic works, as these works show the features and characteristics of the folklore and cultural heritage that the city of (Dachi-Zhou) has preserved until now.